Using artificial illumination to survey nocturnal reef fish - Fitzpatrick, C.; McLean, D.; Harvey, Euan (Elsevier BV, 2013)
Effects of three different light wavelengths (blue, red and white) were assessed on the composition, abundance and behaviour of nocturnal fish at the Houtman Abrolhos Islands, Western Australia. The effects of fishing were also considered by further examining the combined effects of lighting and fishing (open vs. closed areas). Data were collected using baited remote underwater stereo-video systems (stereo- BRUVs), which were equipped with red (620–630 nm), white (550–560 nm) or blue (450–465 nm) lights. The total number of individuals, relative abundance of fish and assemblage composition differed under each lighting condition and fishing status. The greatest number of individuals was observed on samples illuminated by red lights (43% of all individuals surveyed). The species Apogon doederleini, Gymnothorax woodwardi, and Pempheris klunzingeri were each more abundant and spent longer in the field of view of the cameras using red lights. In contrast to white and blue light, the wavelength of red light is thought to be beyond the visual sensitivity of these fish species, and may not have affected their behaviour. The heavily targeted species, Pagrus auratus, were twice as abundant on stereo-BRUVs illuminated by blue lights and white lights than on red lights, but only in areas closed to fishing. This higher abundance on blue and white lights may have been due to the attraction of baitfish to these lights. In addition to the effects of lighting, clear effects of fishing were noted on nocturnal populations of P. auratus. Light wavelength can influence observations and measurements made of a nocturnal fish assemblage, and therefore careful consideration of choice of light wavelength should be made for nocturnal studies using artificial illumination on stereo-BRUVs.